Excessive alcohol use and drug overdose deaths, New Mexico, 2015-2016. (1st October 2020) - Mahdi, Ihsan; Tomedi, Laura E.; Gerrard, Chandra Y.; Lathrop, Sarah; Landen, Michael
Highlights: Alcohol is involved in approximately 1 in five overdose deaths in New Mexico. Certain decedent groups were more likely to have had a BAC ≥ 0.08 g/dL. Abstract: Background: Excessive alcohol use is an important component of a person's risk for drug overdose death. But alcohol's contribution to overdose death risk has not been well quantified. We aimed to quantify the role of excessive alcohol use, particularly as defined by a blood alcohol concentration (BAC) ≥0.08 g/dL, in drug overdose deaths in New Mexico (NM). Methods: The study was conducted in 2018. We abstracted death records (scene investigation, toxicology, pathology) for all drug overdose deaths in NM during 2015–2016, information on BAC, other indications of alcohol, risk factors, comorbidities, and drug type and linked this information with demographic characteristics on death certificates. A Poisson regression model was used to determine independent associations between decedents' characteristics and alcohol involvement among drug overdose decedents. Results: Approximately 18 % (n = 170) of the 946 drug overdose decedents in this study had a BAC ≥ 0.08 g/dL. After adjustment, drug overdose decedents who were American Indian/Alaska Native or had a history of alcohol use disorder were more likely to have had a BAC ≥ 0.08 g/dL at the time of death. However, decedents who had methamphetamine involved in their death or who had a history of diabetes, mental illness, or chronic pain were less likely to have a BAC ≥ 0.08 g/dL at the time of death. Conclusions: Nearly 1 in 5 overdose decedents had a BAC ≥ 0.08 g/dL at the time of death, suggesting that evidence-based alcohol prevention strategies (e.g., increasing alcohol taxes, regulating alcohol outlet density) could reduce the risk of drug overdose death.